Emergent hypercongestion in Vickrey bottleneck networks - Dario Frascaria; Neil Olver; Erik T. Verhoef (Tinbergen Institute, 2020)
Hypercongestion - the phenomenon that higher traffic densities can reduce throughput - is well understood at the link level, but has also been observed in a macroscopic form at the level of traffic networks; for instance, in morning rush-hour traffic into a downtown core. In this paper, we show that macroscopic hypercongestion can occur as a purely emergent effect of dynamic equilibrium behaviour on a network, even if the underlying link dynamics (we consider Vickrey bottlenecks with spaceless vertical queues) do not exhibit hypercongestion.
Keywords: D62; R41; R48; 330; Hypercongestion; Vickrey bottlenecks; Spaceless vertical queues; Arbitrary networks; Homogeneous users; Optimal (first-best) pricing